A Misdiagnosed Metastatic Squamous Cell Carcinoma of the Vulva - Brambullo, Tito; Azzena , Gian Paolo; Masciopinto, Giuseppe; Toninello, Paolo; Biffoli, Bernardo; De Lazzari, Alberto (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Early diagnosis of vulvar squamous cell carcinoma (SCC) is directly related to better prognosis and higher survival rate. Missed gynecologist follow-up, some cultural traditions and refrain from facing with a problem that involves intimacy and sexual sphere can be the cause of delayed diagnosis and treatment. Radical surgery still represents the gold standard, but narrow excision margins can progressively lead to local recurrence, even after years. CASE REPORT: The case we present is a rare case of misdiagnosed metastatic SCC of the vulva after radical excision and groin dissection 2 years before. After a full-through discussion with patient on treatment options and prognosis, a multidisciplinary surgical approach was planned, consisting in wide surgical resection of groin, part of mons pubis and right pelvic iliac-obturator lymphadenectomy. Femoral artery excision was performed due to absence of a clear margin, and reconstruction was accomplished with interposed great saphenous vein graft. The plastic reconstruction consisted in harvest of transverse rectus abdominal flap (TRAM), that was transposed inferiorly to repair right groin. Pathologist confirmed free margins of excision and pelvic lymph nodes resulted negative (pT1b, N3, M0 – stage IV A). DISCUSSION: When deep structures of the groin - such as femoral vessels - are involved by relapse, the condition is potentially life-threatening. A multidisciplinary approach consents to perform a radical surgery with free margins and likewise to achieve a satisfying functional reconstruction. CONCLUSION: This case should emphasize that skin ulceration on a non-weight-bearing surface is always suspicious for skin malignancy, an incisional biopsy is easy to perform and consents a rapid diagnosis. A history of recurrent vulvar SCC should always warn about the risk of late lymph node metastasis even years after a radical excision of the primary tumor and concomitant lymphadenectomy.